X-Ray Fluorescence Spectrometry and Its Applications to Archaeology : An Illustrated Guide - Donais, Mary Kate (Momentum Press, 2018)
Cover -- Contents -- List of Figures -- List of Tables -- Preface -- Acknowledgments -- Chapter 1: Theory and Basic Principles -- Chapter 2: Instrumentation -- Chapter 3: Data Collection -- Chapter 4: Considerations for Data Collection in the Field -- Chapter 5: Data -- Chapter 6: Pigments -- Chapter 7: Ceramics -- Chapter 8: Glass -- Chapter 9: Construction Materials -- Chapter 10: Metallurgical Materials -- Summary -- About the Authors -- Index -- Adpage -- Backcover.